K-12 Teachers work stress: a systematic review of journal articles published from 2011 to 2022 - Yohannes Bisa Biramo; Zhenhong Wang (Al-Qanṭara, 2024)
This study reviewed research papers in the Web of Science database published between 2011 and 2022. The review synthesized K–12 teacher work stress literature and summarized methods and limitations to analyse trends in the area. The review showed that the basic contents investigated in the published articles are stress copying strategies, stress reduction interventions, and the effects of work stress on teachers' personal characteristics. Besides, a limited number of studies on K–12 teacher’s work stress were also observed. In terms of research methods, a significant proportion of published papers employed quantitative research methodologies, followed by qualitative and mixed-method studies. Most of the reviewed articles were conducted in elementary and secondary schools in conjunction. Self-report methods are only suited for assessing teachers' subjective psychological stress, not biological stress. Further studies should integrate subjective and biological stress measurements using ambulatory assessment methods to analyse stress in authentic educational settings.